Challenges to the adjudicator's decision - Tan, Sean Git (2007)
Statutory adjudication has been widely adopted in several commonwealth countries. Malaysia too is currently considering its own model on statutory adjudication. It is usually anticipated that the adjudicator's decision binds the parties unless one of the parties chooses to challenge it. However, it is difficult to find express provisions in the various legislations that spell out grounds for challenges to an adjudicator's decision. There have been, however, court decisions on whether adjudicators' decisions may or may not, as a matter of principle, be challenged. This research seeks to examine the possible grounds of challenges to the adjudicator's decision and to establish the extent of success of such challenges based on court decisions. The analysis shows various grounds of challenges that are available to the aggrieved parties to resist enforcement of the adjudicator's decision. These have been categorised in six areas in this research. It is found that in considering whether there are valid grounds for the aggrieved party to challenge the decision, the courts do not generally look at the merits of the dispute; these are rarely discernible. However, the question remains: what is the jurisdiction and authority of the adjudicator? Not only must the adjudicator have jurisdiction to act; in conducting the proceedings he must also be unbiased and fair - he is to follow the rules of natural justice?. The challenges to the enforcement may also be brought up on the grounds of concurrent court proceedings, insolvency, and set-off, but they are unlikely to succeed. The courts have in some instances adopted a more cautious approach to the enforcement of adjudication. However, the extent of success in which the grant and refusal of enforcement still depends on the merits of each case.